2014
DOI: 10.7567/jjap.53.06jm05
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature hermetic sealing by ultrasonic bonding with Au compliant rim

Abstract: We newly introduce a compliant rim to realize hermetic sealing of electronic components at low temperature. The compliant rim easily deforms under pressing load owing to its cone-shaped cross section and, therefore, intermetallic bonding can be performed at low temperature. We demonstrate the room-temperature vacuum sealing using the compliant rim made of Au with the aid of ultrasonic vibration of submicron amplitude. A test vehicle fabricated using silicon and glass showed that the air leak rate of the room-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…This test is simple and a good indicator of gas leakage. (32) Figure 6(b) shows an optical microscopy image of a sealed area after immersing it in water. The dark and bright areas represent penetrated water and air, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This test is simple and a good indicator of gas leakage. (32) Figure 6(b) shows an optical microscopy image of a sealed area after immersing it in water. The dark and bright areas represent penetrated water and air, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(30,31) Recently, RT vacuum packaging has been demonstrated using compliant rims made of Au with ultrasonic assist. (32) A large Au-Au bonding strength could be achieved, and the ability of the compliant rim was experimentally verified. Therefore, we have focused on compliant rims made of Cu.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Low-temperature bonding techniques have been extensively studied for the packaging of MEMS assemblies to suppress thermal damage [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Particularly, atomically smooth Au surfaces can form atomic bonds at room temperature [ 8 , 9 , 10 ], which enables the integration of dissimilar materials regardless of the mismatches in the coefficient of thermal expansion. It has been demonstrated that wafers coated with Au/Ti (from top to bottom) bonding layers can form vacuum packaging at room temperature [ 11 ].…”
Section: Introductionmentioning
confidence: 99%